Injury and Skeletal Biomechanics - Goswami, Tarun (IntechOpen, 2012)
This book covers many aspects of Injury and Skeletal Biomechanics. As the title represents, the aspects of force, motion, kinetics, kinematics, deformation, stress and strain are examined in a range of topics such as human muscles and skeleton, gait, injury and risk assessment under given situations. Topics range from image processing to articular cartilage biomechanical behavior, gait behavior under different scenarios, and training, to musculoskeletal and injury biomechanics modeling and risk assessment to motion preservation. This book, together with "Human Musculoskeletal Biomechanics", is available for free download to students and instructors who may find it suitable to develop new graduate level courses and undergraduate teaching in biomechanics.